Produção e caracterização de bio-óleo proveniente da torta da Moringa oleifera Lam. - Maciel, Samia Tássia Andrade (2015)
Although they have been found new oil fields, the fossil fuels are finite and non-renewable resources. New sources of renewable energy are being researched as an alternative source to replacement of fossil fuels. The advantages of renewable resources and low cost, in favor of sustainability, accelerated the development and use of biomass for the diversified production of chemical products, allowing a lower fossil fuel dependence with the benefits resulting of ecological and economic point of view. The thermal degradation of lignocellulosic materials is one of the most promising avenues for obtaining energy sources and chemical products from biomass. The pyrolysis is the main thermochemical conversion method where the organic material is converted by heating under an inert atmosphere in gases, condensable gases (recovered as product liquid) and a solid (char). In this study, the seeds and seed waste Moringa oleifera Lam. obtained through the oil extraction with solvent and pressing, they were named as chemical and mechanical cakes, they were investigated as a potential source for bio-oil production. The chemical and thermochemical characterization of biomass were conducted through the oil content analysis, moisture, ash, volatile, structural analysis and thermogravimetry. The calorific value of the biomass ranged between 17 and 21 MJ / kg. The initial results showed that the biomass of M. oleifera can potentially produce energy by thermochemical conversion processes. Based on the optimization of the pyrolysis conditions in a fixed bed reactor, for biomass powder, the temperature of 600 °C and N2 flow of 1 ml / min were chosen, where the yields obtained were 20,29, 24,61 and 55,09 % for the liquid phase (aqueous phase + bio-oil), biochar and biogas, respectively. The chromatographic analysis of bio-oil seed powder was possible to identify and to quantify the chemical classes present in bio-oil, where a high content of carboxylic acids was observed with approximately 70% of area percent, the remainder being assigned to nitrogen function, phenols, hydrocarbons, among others. For the GC/MS analysis bio-oils from the biomass pellets, the carboxylic acids were also found in higher concentrations for bio-oils of seed, mechanical and ultrasound cakes with contents from 21 to 27 % for oleic and linoleic acids. However for the Soxhlet cakes, the higher concentration of phenolics and nitrogen function with a percentage of 43% was obtained in both. Therefore, the bio-oil Moringa exhibited good results for the industrialization and it can be applied in industry as flavorings, resins, pesticides and fertilizers.